PERAN KEPEMIMPINAN DIGITAL KEPALA SEKOLAH DALAM MENGOPTIMALKAN PEMBELAJARAN BERBASIS TEKNOLOGI - Frizdew, Besta Rahma; Arifah, Wafda; Gistituati, Nurhizrah; Rusdinal, Rusdinal; Nellitawati, Nellitawati (STKIP Pesisir Selatan, 2025)
Digital leadership requires headteachers not only to understand the use of technology, but also how it can be utilised to improve efficiency, teaching quality, and student learning outcomes. The digital era has transformed the role of headteachers from traditional managers to digital leaders who facilitate, direct, and accelerate the integration of technology in learning. This literature review article examines the concept of digital leadership in school principals, its main dimensions (digital vision, teacher professional development, resource and data management, innovation culture, ethics & data security), and the mechanisms by which such leadership influences technology adoption and the quality of technology-based learning. The study utilises empirical literature and a systematic review of publications from 2015–2025 to formulate a conceptual model and practical recommendations for policymakers and school practitioners. Findings indicate that effective digital leadership combines strategic vision, teacher capacity building, data management policies, and a collaborative culture which significantly improve the readiness and quality of technology-based learning